Young Workers’ Perceptions of Trade Unions in Portugal - Kovács, Ilona; Dias, João; da Conceição Cerdeira, Maria (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2017)
This paper seeks to capture how unions are perceived by young workers in Portugal and to identify different types of perceptions. Our analysis considers both structural factors and subjective experiences and is based on semi-structured interviews with young people working in sectors with a high concentration of youth employment. The fact that young workers are increasingly exposed to the pressures of unemployment and precarious work might suggest that there is homogeneity in their perceptions about trade unions and collective action. However, our results show that young workers’ perceptions are not homogenous and that they interconnect with distinct segments, characterized by different socio-economic conditions, as defined by family status, education level and position in the labour market. Three types of perceptions were identified by content analysis of the interviews: positive, negative and critical perceptions. A final segment of younger and less-skilled workers, of families with low educational and economic resources and having left school prematurely, have neither information nor any understanding about unions.Our findings support the thesis that diversity of educational and early labour market experiences, which characterize transition processes to adulthood, shape the relation between young workers and unions, in particular the motivation to join unions. Capturing the diversity of young workers experiences and perceptions is a challenge to industrial relations research, as well as to trade unionism. It can provide unions with important insights into how to adapt their strategies to recruit new young members and to mobilize the latent interests of young workers in collective action.